Mark Twain e os boy - books: outros espaços da infância em suas reescrituras na literatura e no cinema - Silva, Jardas de Sousa (2024)
This doctoral thesis explores the theme of childhood protagonism in the works of Mark Twain and their cinematic adaptations, particularly in The Adventures of Tom Sawyer (1876) and The Adventures of Huckleberry Finn (1885). Through a comparative literature approach, it investigates how these narratives, recognized as boy-books, capture the complexities of childhood and challenge 19th-century moral conventions. The research also examines how the values and behaviors of the main characters, Tom and Huck, were reinterpreted in cinema, outlining a panorama of the rebellious and transgressive childhood of American "bad boys" and their sociocultural dynamics. Among the primary objectives, the study aims to understand how cinematic adaptations relate to the source text and how they bring themes of childhood, friendship, and morality to the screen. The thesis examines, through the adaptations The Adventures of Tom Sawyer (1938), directed by Norman Taurog, and The Adventures of Huck Finn (1993), directed by Stephen Sommers, the differences in cinematic strategy and critical reception over time, reflecting the evolving social view of childhood and rebellion. Theoretically, the research draws on authors such as André Lefevere (2007), Linda Hutcheon (2013), and Robert Stam (2008) to establish film adaptation as a form of intersemiotic translation. Additionally, studies on children's literature and cinema by Marcia Ann Jacobson (2014), Douglas Street (1982), and Jack Zipes (2012) are essential for contextualizing the evolution of childhood representation in U.S. cinema and its impact on young audiences. Through this investigation, we hope to construct a profile of Twain's adaptations that highlights how the moral and social dilemmas represented in his boy-centered works remain relevant and are reinterpreted across different times and contexts. Thus, we also aim to contribute to the understanding of literary adaptations as dynamic cultural processes, with aesthetic and ideological implications that enhance the perception of cultural phenomena associated with childhood and its representation in literature and cinema.